2004
DOI: 10.4141/p03-071
|View full text |Cite
|
Sign up to set email alerts
|

How well do early-generation quality tests predict flour performance?

Abstract: . 2004. How well do early-generation quality tests predict flour performance? Can J. Plant Sci. 84: 71-78. A wide range of flours varying in protein content, strength and baking quality were used to investigate the relationship between early-generation screening tests at the Cereal Research Centre, advanced generation testing at the Grain Research Laboratory (GRL) and pilot-scale commercial testing at the Canadian International Grains Institute (CIGI) and Warburton Foods Ltd. Correlations among flour protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…(1999) found that the commercial‐scale (524‐g dough) compared with small‐scale tests (dough of 100 g) made with white flour, even under long fermentation conditions, would not be very powerful ( r = 0.63) to predict the baking performance of cultivars. Kaur et al . (2004) showed instead that the correlation between small‐ and large‐scale would be good for baking tests with short fermentation periods, about 60–75 min in total, while Preston et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1999) found that the commercial‐scale (524‐g dough) compared with small‐scale tests (dough of 100 g) made with white flour, even under long fermentation conditions, would not be very powerful ( r = 0.63) to predict the baking performance of cultivars. Kaur et al . (2004) showed instead that the correlation between small‐ and large‐scale would be good for baking tests with short fermentation periods, about 60–75 min in total, while Preston et al .…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, Graybosch et al (1999) found that the commercial-scale (524-g dough) compared with smallscale tests (dough of 100 g) made with white flour, even under long fermentation conditions, would not be very powerful (r = 0.63) to predict the baking performance of cultivars. Kaur et al (2004) showed instead that the correlation between small-and large-scale would be good for baking tests with short fermentation periods, about 60-75 min in total, while Preston et al (1997) stated that the cultivar performance would vary much under such experimental conditions (rapid bread making). Since the industry does not use a scheduled time for the processing of the dough, baking laboratory tests would be useful to monitor changes in quality of flour (Cauvain, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, micro-methods are used to determine the quality characteristics (Belitz et al, 1978;Kaur et al, 2004). Several down-scaled versions of the common wheat-analyzing tools, such as Extensograph and Farinograph, have been developed (Kieffer et al, 1998;Kaur et al, 2004). Nevertheless, baking tests are still the best quality-prediction tool to determine baking properties of wheat flour.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sample sizes in early generation grain-breeding and testing of newly tailored baking additives are limited. Therefore, micro-methods are used to determine the quality characteristics (Belitz et al, 1978;Kaur et al, 2004). Several down-scaled versions of the common wheat-analyzing tools, such as Extensograph and Farinograph, have been developed (Kieffer et al, 1998;Kaur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%